Proceeding the 2 nd international seminar on chemical education, Yogyakarta September 12-13 th 2017 - INTERNATIONAL SEMINAR on CHEMICAL EDUCATION 2017 (2 nd : 2017 : Yogyakarta) (Fakultas MIPA UII, 2017)
xiii, 400 halaman : ilustrasi ; 29 cm